Nursing research on intimate partner violence in China: A scoping review - Quanlei Li; Huaping Liu; Kuei-Ru Chou; Chia-Chin Lin; Iat-Kio Van; Patricia M. Davidson; Jacquelyn C. Campbell (Elsevier, 2020)
Summary: Intimate partner violence (IPV) is a serious public health issue, and nurses have the potential to screen, navigate to interventions, and provide support, but responses to IPV differ greatly in mainland China, Hong Kong, Macao, and Taiwan. We conducted a scoping review to examine the nursing literature on IPV in the above four regions in China. We conducted a comprehensive search of 11 Chinese and English databases from database inception to January 31, 2020, for eligible papers including empirical studies, reviews, reports, and expert opinion articles. We hand searched references lists and other studies published by the first and corresponding authors of included articles. Two reviewers independently screened articles and extracted data, and three reviewers cross-checked the extracted results. We also conducted quality appraisal for applicable empirical studies. A total of 58 Chinese-language and 63 English-language articles were included, 58 from Taiwan, 44 from Hong Kong, 13 from mainland China, and six from institutions outside China, but none from Macao. The quantitative and qualitative studies described the prevalence and complex nature of IPV, comparable to non-nursing and international studies. Nurse-led advocacy and Qigong (traditional Chinese mind-body health practice) interventions showed promise for improving mental health in women in Hong Kong. There was a low level of knowledge and preparedness to respond to IPV among Chinese nurses, especially in mainland China. Mixed methods studies in Hong Kong and Taiwan as complex designs were generally well-conducted. Nursing case reports from Taiwan uniquely supplemented the evidence base. In Hong Kong and Taiwan, varying designs were used to study various facets of IPV, targeting victims, nurses and other key stakeholders. In mainland China and Macao, IPV research was limited in quantity, quality, and diversity. As more research in the area of IPV is needed, factors influencing nursing research on IPV also merit investigation, while taking into consideration socio-economic-political-cultural factors.